2021
DOI: 10.3389/fmicb.2021.692474
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Attenuates Quorum-Sensing Regulated Virulence and Biofilm Formation in Pseudomonas aeruginosa

Abstract: With the prevalence of multidrug-resistant bacteria and clinical -acquired pathogenic infections, the development of quorum-sensing (QS) interfering agents is one of the most potential strategies to combat bacterial infections and antibiotic resistance. Chinese herbal medicines constitute a valuable bank of resources for the identification of QS inhibitors. Accordingly, in this research, some compounds were tested for QS inhibition using indicator strains. Paeonol is a phenolic compound, which can effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…Therefore, in the following study, 70% ethanol extracts of A. pilosa were used. Sd the QS system regulates most of the virulence factors and pathogenicity [ 7 , 23 ], we further examined the effects of the extracts from A. pilosa on the virulence phenotypes of PAO1.The virulence-related phenotypes, including motility (twitching, swimming, and swarming), elastase and pyocyanin production, and biofilm formation, were reduced when different concentrations of the 70% ethanol extracts of A. pilosa were used ( Figure 1 B). The pathogenicity detection by the Chinese cabbage model showed that the decay area gradually became small with the increase of the extract concentrations of A. pilosa ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the following study, 70% ethanol extracts of A. pilosa were used. Sd the QS system regulates most of the virulence factors and pathogenicity [ 7 , 23 ], we further examined the effects of the extracts from A. pilosa on the virulence phenotypes of PAO1.The virulence-related phenotypes, including motility (twitching, swimming, and swarming), elastase and pyocyanin production, and biofilm formation, were reduced when different concentrations of the 70% ethanol extracts of A. pilosa were used ( Figure 1 B). The pathogenicity detection by the Chinese cabbage model showed that the decay area gradually became small with the increase of the extract concentrations of A. pilosa ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the extracts from the mixture of Artemisiae argyi folium, the root bark of Cortex dictamni , and the root of Solanum melongena could completely inhibit pqs system of P. aeruginosa [ 21 ]. Paeonol from peony root interfered with las system, reduced virulence production, and inhibited biofilm formation [ 23 ]. Coumarin, a Chinese medicinal herb-derived phenolic compound, reduced protease and pyocyanin production and inhibited biofilm formation of different P. aeruginosa strains by impairing QS systems and changing cyclic diguanylate (c-di-GMP) metabolism [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAO1 significantly inhibited macrophages cell proliferation, induced cytotoxic responses, and led to cell membrane damage and rupture, lysis, and death. Our former studies had revealed that paeonol could attenuate quorum-sensing regulated virulence and biofilm formation in P. aeruginosa and show a protective effect on C. elegans infected with P. aeruginosa in vivo ( 28 ). Here, the potential therapeutic effect and mechanism of paeonol were investigated in a macrophage infected with a PAO1 cell model.…”
Section: Discussionmentioning
confidence: 99%
“…Paeonol is a polyphenolic compound originally extracted from Paeonia lactiflora , Moutan cortex , and Cynanchum paniculatum , which has been used wildly due to various medicinal benefits as an analgesic, antipyretic, and anti-inflammatory agent in traditional Chinese medicine ( 26 , 27 ). Previous studies have demonstrated that paeonol attenuates quorum-sensing, inhibits virulence factors, and biofilm formation ( 28 ). Paeonol has been well-documented for revealing potential anti-inflammatory activity in macrophages ( 29 , 30 ), but the possible mechanism by regulating virulence and inflammation to reduce pathological damage upon pathogenic P. aeruginosa infection has not yet been fully studied in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The qRT-PCR reaction was conducted on a LightCycler ® 480II Master Mix (Roche, Germany). Data from qRT-PCR experiments were analyzed using the 2 ®-ΔΔCT method ( Yang et al, 2021 ). Primer sequences are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%